Proximal C-Terminus Serves as a Signaling Hub for TRPA1 Channel Regulation via Its Interacting Molecules and Supramolecular Complexes - Zimova, Lucie; Barvikova, Kristyna; Macikova, Lucie; Vyklicka, Lenka; Sinica, Viktor; Barvik, Ivan; Vlachova, Viktorie (Frontiers in Physiology, 2020)
Our understanding of the general principles of the polymodal regulation of transient receptor potential (TRP) ion channels has grown impressively in recent years as a result of intense efforts in protein structure determination by cryo-electron microscopy. In particular, the high-resolution structures of various TRP channels captured in different conformations, a number of them determined in a membrane-mimetic environment, have yielded valuable insights into their architecture, gating properties and the sites of their interactions with annular and regulatory lipids. The correct repertoire of these channels is, however, organized by supramolecular complexes that involve the localization of signaling proteins to sites of action, ensuring the specificity and speed of signal transduction events. As such, TRP ankyrin 1 (TRPA1), a major player involved in various pain conditions, localizes into cholesterol-rich sensory membrane microdomains, physically interacts with calmodulin, associates with the scaffolding A-kinase-anchoring protein (AKAP) and forms functional complexes with the related TRPV1 channel. This perspective will contextualize the recent biochemical and functional studies with emerging structural data with the aim of enabling a more thorough interpretation of the results, which may ultimately help to understand the roles of TRPA1 under various physiological and pathophysiological pain conditions. We demonstrate that an alteration to the putative lipid-binding site containing a residue polymorphism associated with human asthma affects the cold sensitivity of TRPA1. Moreover, we present evidence that TRPA1 can interact with AKAP to prime the channel for opening. The structural bases underlying these interactions remain unclear and are definitely worth the attention of future studies.